Development of professional motivation of future doctors and pharmacists in the process of formation of the IT competence - Dobrovolska, А. (Problems of Engineer-Pedagogical Education, 2018)
In the article, attention has been focused on the concept of «рrofessional motivation». We have described the professionally-oriented motives, which are present in the process of formation of information technology competence (the IT competence) of future doctors and pharmacists during teaching the disciplines of naturally scientific preparation. The method of evaluation of levels of professional motivation of the future specialists in the process of formation of their IT competence during teaching the disciplines of naturally scientific preparation has been developed, which foresees the questionnaire survey of subjects of the educational process on the formulated questions and implementation of the algorithm of evaluation of its results with the use of the appropriate statistical methods. We have conducted the questionnaire survey of the research subjects and also estimated its results provided by the foreseen algorithm within the limits of the developed method. It has been found, that the process of formation of the IT competence during teaching the disciplines of naturally scientific preparation with the use of the developed manuals is crucial for development of professional motivation of future doctors and pharmacists.